Implementasi Layanan Administrasi Laporan Kerja Praktik dan Laporan Akhir Mahasiswa Berbasis Web Menggunakan Aplikasi SIABI di Jurusan Bahasa dan Pariwisata - Kusuma, Octa Angga; Ramadona, Ongky; Wahyudi, Muhammad (Teknik Komputer Politeknik Negeri Sriwijaya, 2025)
The administrative process for student reports related to Internships and Final Reports in the Language and Tourism Department is currently still done manually, making it inefficient and often leading to errors in writing letters and formatting inconsistencies between the resulting letters. The process of creating these letters takes approximately 3-5 working days depending on the presence of the head of the department who signs them, so students must continuously monitor the progress of the letters by visiting the department. To address this, a web-based SIABI application was developed. In comparison, through the SIABI Application, the service waiting time is targeted to be 1-2 working days with the ease of tracking the status of letter submissions through the application dashboard without the need to come to the department and prevent format inconsistencies between the letters submitted and those produced by the department. The method used in developing this application is the Waterfall R&D model. The results of the study indicate that the implementation of the SIABI application can provide convenience for students in submitting letters online, reduce the potential for errors, facilitate real-time tracking of letter statuses, and improve the accuracy of student administrative services.